2021
DOI: 10.1007/978-3-030-74486-1_7
|View full text |Cite
|
Sign up to set email alerts
|

A Quaternion Deterministic Monogenic CNN Layer for Contrast Invariance

Abstract: Deep learning (DL) is attracting considerable interest as it currently achieves remarkable performance in many branches of science and technology. However, current DL cannot guarantee capabilities of the mammalian visual systems such as lighting changes. This paper proposes a deterministic entry layer capable of classifying images even with low-contrast conditions. We achieve this through an improved AQ1 version of the quaternion monogenic wavelets. We have simulated the atmospheric degradation of the CIFAR-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In [36], the authors reported a cortical adaptation to brightness and darkness in the macaque primary visual cortex V1. In relation to this, it is worth mentioning that the experimental results of the present work confirm the expectation advanced in [30,29,25] that the local phase and local orientation should be invariant with respect to brightness and contrast changes due to its geometry representation.…”
Section: Bio-inspired Properties and Toolssupporting
confidence: 90%
See 2 more Smart Citations
“…In [36], the authors reported a cortical adaptation to brightness and darkness in the macaque primary visual cortex V1. In relation to this, it is worth mentioning that the experimental results of the present work confirm the expectation advanced in [30,29,25] that the local phase and local orientation should be invariant with respect to brightness and contrast changes due to its geometry representation.…”
Section: Bio-inspired Properties and Toolssupporting
confidence: 90%
“…A previous version of the M6 layer, still deterministic, was presented in [25], but already with quite robust responses for illumination or contrast variations. In another recent work [19], the authors propose a bio-inspired approach to leverage quaternion Gabor filters to improve the classification even with contrast degradations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation